Chinese international students’ collective navigation of their study abroad experiences: Analysis of Xiaohongshu posts about UK university life - McLean, Neil; Purton, Iga; Tan, Wenyu; Zhng, Jiuyu (Journal of International Students, 2026)
This study explores the experiences of Chinese international students at London universities by analyzing 1,791 Mandarin-language posts from the Xiaohongshu site (RedNote). Six interconnected themes were identified in this naturally occurring discourse, reflecting the topics and concerns that these students themselves considered important. The themes are community and social life; identity and belonging; academic adaptation; future planning and uncertainty; managing daily life; and navigating structural and institutional systems. A key observation from this analysis lies in these students’ use of social media to transform individual experiences and struggles into a kind of ‘collective navigation’ of the challenges and meanings of being an international student. This was accomplished through the extensive use of cultural capital to broker shared understandings and transform individual psychological experiences into a distributed social process of acculturation and withdrawal. This provides a new framework for understanding sojourner adaptation in academic settings.